The End of the Partnership With a Guide Dog: Emotional Responses, Effects on Quality of Life and Relationships With Subsequent Dogs - Lloyd, Janice; Budge, Claire; La Grow, Steve; Stafford, Kevin (Frontiers in Veterinary Science, 2021)
Guide dogs are mobility aids that facilitate independent travel of people who are blind or visually impaired. Additional benefits imparted to the guide dog handler include companionship, and increased: social-function, self-esteem and confidence. Some evidence shows that the end of the guide dog partnership can result in reduced mobility, and may have profound psychosocial effects on the handler due to feelings of bereavement and loss of self-esteem. However, this evidence is limited. This study examined the experiences and feelings of 36 people across New Zealand, who experienced the ending of at least one partnership with a guide dog (77 pairings), to explore issues arising at the end of the partnership and how this may impact on relationships with subsequent dogs. Results indicate that the majority of handlers experienced a reduction in their quality of life due to a decrease in independent mobility followed by the loss of a friend and companion, curtailment of social interactions, and loss of self-esteem/confidence. The end of the partnership affected people in different ways. Most handlers “accepted” the partnership had ended, but some felt guilty or angry with the guide dog school. Most applied for another dog immediately, as the need for mobility was high, while others preferred to wait and a smaller number did not reapply. Feelings at this time also affected the handlers' relationships with subsequent guide dogs, with over a quarter expressing a negative effect. Retiring a guide dog (for whatever reason) is not only difficult for the handler, but also for the handler's family, friends, co-workers, and doubtlessly, the dog. The majority of handlers expressed feelings of extreme grief when the partnership ended, whether it was successful or not. Feelings of extreme grief were more common for first than subsequent dogs. The depth of emotion was compared to losing a family member or other loved one, which has been reported in some person and pet relationships. A better understanding of issues surrounding the end of the partnership, including the human-animal bond, will help inform the guide dog industry of how best to support their clients during this time and when transitioning to another dog. Findings may be applied to other service/assistance dog users and the pet owning community.